A Laboratory Study on the Molecular Basis of Primary Congenital Glaucoma - Grand Chikezie Ihesiulor; Forbes Manson; Udo Ahanna Ubani (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2018)
Purpose: To detect pathogenic mutations in cytochrome P450 family1 subfamily B polypeptide1 (CYP1B1) gene in nineteen sporadic Primary congenital glaucoma (PCG) cases and to identify patients lacking CYP1B1 mutations. Methods: CYP1B1 exon 2 and the coding part of exon 3 of 15 participants were amplifi ed by Polymerase chain reaction and amplicons were sequenced by Sanger sequencing. Sequencing data was analyzed to identify the gene mutations or Single Nucleotide Polymorphisms SNPs. Results: Four previously reported PCG-associated CYP1B1 mutations (c.1159G>A; p.E387K, c.230T>C; p.L77P, c.1103G>A; p.R368H and c.1568G>A; p.R523K) were found in four patients out of the 15 fully 'sequenced' patients. Also, ten previously reported Single Nucleotide Polymorphisms and two novel noncoding variants were identifi ed. Conclusion: The relatively low percentage of PCG patients having CYP1B1 mutations (4/15=26.6%) demonstrates that other known and unknown genes may contribute to PCG pathogenesis. Lack of CYP1B1 gene mutations in some patients stresses the need to identify other responsible candidates.